Fresh Eyes: Young v. State’s New Eyewitness Identification Test and Prospects for Alaska and Beyond - Best, Savannah Hansen (2018)
This Note evaluates recent developments in Alaska’s eyewitness identification admissibility doctrine under the 2016 case Young v. Alaska. For the past four decades, federal and most state courts have relied on the Supreme Court’s 1977 ruling in Manson v. Brathwaite, which identified five admissibility factors—known as the “Biggers factors”—for establishing the reliability of eyewitness identifications made under the influence of unnecessarily suggestive police procedures (“systemic variables”). In recent decades, however, social and psychological science has demonstrated the flaws in the five Biggers factors as reliability indicators and the impact of non-suggestive circumstantial (or “estimator”) variables on eyewitness identification reliability. In Young , Alaska joined New Jersey and Oregon as the third state to break from Brathwaite, employing a new and evolving admissibility test with scientific support, consideration of both systemic and estimator variables, and a call for corresponding jury instructions